Genomic characterization of a large plasmid containing a bla(NDM-1) gene carried on Salmonella enterica serovar Indiana C629 isolate from China - Wang, Wei (BMC Infect Dis, 2017)
BACKGROUND: The bla (NDM-1) gene in Salmonella species is mostly reported in clinical cases, but is rarely isolated from red and white meat in China. METHODS: A Salmonella Indiana (S. Indiana) isolate was cultured from a chicken carcass procured from a slaughterhouse in China. Antimicrobial susceptibility was tested against a panel of agents. Whole-genome sequencing of the isolate was carried out and data was analyzed. RESULTS: A large plasmid, denoted as plasmid pC629 (210,106 bp), containing a composite cassette, consisting of IS26-bla (NDM-1)-ble (MBL) -△trpF-tat-cutA-ISCR1-sul1-qacE△1-aadA2-dfrA12-intI1-IS26 was identified. The latter locus was physically linked with bla (OXA-1), bla (CTX-M-65), bla (TEM-1)-encoding genes. A mercury resistance operon merACDEPTR was also identified; it was flanked on the proximal side, among IS26 element and the distally located on the bla (NDM-1) gene. Plasmid pC629 also contained 21 other antimicrobial resistance-encoding genes, such as aac(6′)-Ib-cr, aac(3)-VI, aadA5, aph(4)-Ia, arr-3, blmS, brp, catB3, dfrA17, floR, fosA, mph(A), mphR, mrx, nimC/nimA, oqxA, oqxB, oqxR, rmtB, sul1, sul2. Two virulence genes were also identified on plasmid pC629. CONCLUSION: To the best of our knowledge, this is the first report of bla (NDM-1) gene being identified from a plasmid in a S. Indiana isolate cultured from chicken carcass in China.